2010
DOI: 10.1117/1.3502666
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of visibility in virtual chromoendoscopy for esophageal squamous carcinoma using a color difference formula

Abstract: Abstract. Computed virtual chromoendoscopy with flexible spectral imaging color enhancement ͑FICE͒ is a new dyeless imaging technique that enhances mucosal and vascular patterns. However, a method for selecting a suitable wavelength for a particular condition has not been established. The aim of this study is to evaluate the color difference method for quality assessment of FICE images of the intrapapillary capillary loop in magnifying endoscopy for esophageal squamous cell carcinoma. The color difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…4). The color difference between cancer and the background mucosa is higher with FICE than with WLI, 34 suggesting that FICE is useful for detection of this cancer. However, any intraepithelial papillary capillary loops (IPCL) are not clearly visualized compared to what is seen with NBI.…”
Section: Esophageal Diseases Using Ficementioning
confidence: 95%
“…4). The color difference between cancer and the background mucosa is higher with FICE than with WLI, 34 suggesting that FICE is useful for detection of this cancer. However, any intraepithelial papillary capillary loops (IPCL) are not clearly visualized compared to what is seen with NBI.…”
Section: Esophageal Diseases Using Ficementioning
confidence: 95%
“…Recently, several superficial esophageal cancers have been detected owing to improvements in digestive endoscopy. Specifically, image-enhanced endoscopy with magnification including narrow-band imaging, BLI, and flexible spectral imaging color enhancement has enabled clear visualization of the microsvasculature of the tumor surface 5 10 11 12 , which led to the discovery that changes in microvasculature reflect the depth of superficial esophageal cancer 2 3 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Ordinary endoscopic pictures are taken by charge-coupled device camera in a regular endoscopy and arithematically processed. Different from NBI system with fixed wavelengths, composite FICE images are generated on a computer which allows viewing of an image taken under light at any suitable wavelength setting for specific condition [26, 27]. Between wavelength 400 nm and 695 nm of visible light, 60 spectral images at 5 nm interval can be selected.…”
Section: Image-enhanced Endoscopy Screening Of Upper Gastrointestimentioning
confidence: 99%
“…The method of selecting a suitable combination of wavelengths of RGB lights for esophageal squamous epithelium has not been well established. Inoue et al have shown that the specific FICE modes A (R 550 nm, gain 2; G 500 nm, gain 2; B 470 nm, gain 3) and C (R 540 nm, gain 2; G 415 nm, gain 2; B 415 nm, gain 3) significantly enhanced the visibility of IPCLs of ESCC mucosa [27]. Some investigators have demonstrated a superior outcome in the diagnostic yield of esophageal capsule endoscopy by combination of the FICE system mode A with the PillCam ESO2 (Given Imaging, Yoqneam, Israel) [59].…”
Section: The Application Of Iee In Esophagusmentioning
confidence: 99%